Neurodevelopmental Delay Diagnosis Rates Are Increased in a Region with Aerial Pesticide Application - Hicks, Steven D.; Wang, Ming; Fry, Katherine; Doraiswamy, Vignesh; Wohlford, Eric M. (Frontiers in Pediatrics, 2017)
A number of studies have implicated pesticides in childhood developmental delay (DD) and autism spectrum disorder (ASD). The influence of the route of pesticide exposure on neurodevelopmental delay is not well defined. To study this factor we examined ASD/DD diagnoses rates in an area near our regional medical center that employs yearly aerial pyrethroid pesticide applications to combat mosquito-borne encephalitis. The aim of this study was to determine if areas with aerial pesticide exposure had higher rates of ASD/DD diagnoses. This regional study identified higher rates of ASD/DD diagnoses in an area with aerial pesticides application. Zip codes with aerial pyrethroid exposure were 37 % more likely to have higher rates of ASD/DD (adjusted RR=1.37, 95% CI=1.06-1.78, p=0.02). A Poisson regression model controlling for regional characteristics (poverty, pesticide use, population density, and distance to medical center), subject characteristics (race and sex), and local birth characteristics (prematurity, low birth-weight, and birth rates), identified a significant relationship between aerial pesticide use and ASD/DD rates. The relationship between pesticide application and human neurodevelopment deserves additional study to develop safe and effective methods of mosquito prevention, particularly as communities develop plans for Zika virus control.